2002
DOI: 10.1159/000057670
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Once-Daily Therapy with Telithromycin for 5 or 10 Days for the Treatment of Acute Maxillary Sinusitis

Abstract: Background: The efficacy and tolerability of oral telithromycin 800 mg once daily for 5 vs. 10 days were assessed in patients with acute maxillary sinusitis (AMS). Methods: Adults (n = 341) with confirmed AMS diagnosed on clinical signs and symptoms and sinus X-ray showing total opacity or air-fluid level were randomized to receive oral telithromycin for 5 days (followed by placebo for 5 days; n = 170) or 10 days (n = 171). Causative pathogens were isolated by pretreatment sinus puncture (day 1). Clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 13 publications
3
43
0
3
Order By: Relevance
“…Conversely, while the efficacy of clarithromycin (79% -91%) and telithromycin (72.9% -91.9%) is high, the incidence of side effects reported in the various studies done has also been shown to be high, with an incidence of 28% -48.4% (17,28,30) and 24.1% -46.9% (11,13,(20)(21)(22) , respectively. Clarithromycin and telithromycin should be used judiciously and their efficacy needs to be balanced against the common side effects.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Conversely, while the efficacy of clarithromycin (79% -91%) and telithromycin (72.9% -91.9%) is high, the incidence of side effects reported in the various studies done has also been shown to be high, with an incidence of 28% -48.4% (17,28,30) and 24.1% -46.9% (11,13,(20)(21)(22) , respectively. Clarithromycin and telithromycin should be used judiciously and their efficacy needs to be balanced against the common side effects.…”
Section: Discussionmentioning
confidence: 98%
“…All studies reviewed used a dose of 800 mg OD. Most studies had a dosing regimen that lasted for 5 days (n = 5) (11)(12)(13)(20)(21)(22) while the rest had a dosing regimen that lasted for 10 days (n = 2) (21,22) . There was no signifi cant diff erence in the effi cacy of using telithromycin 800 mg OD for 10 days over 5 days (10 …”
Section: Telithromycin (Figure 2)mentioning
confidence: 99%
“…44 However, evidence for moxifloxacin and telithromycin suggests that a shorter course of 5-7 days is clinically and/or bacteriologically equivalent to a 10-day course. 45,46 Recent studies have also shown that bacteriological eradication occurs within 72 hours with moxifloxacin (400 mg once daily) or with high-dose, short-course levofloxacin (750 mg once daily for five days). 47,48 This higher dose of levofloxacin improves the PK/PD profile of the agent and in a comparative trial of this dose versus levofloxacin 500mg once daily for 10 days, clinical and microbiological efficacy was found to be similar.…”
Section: Duration Of Antibiotic Treatment For Absmentioning
confidence: 99%
“…Three randomised, controlled trials have been performed in patients with AMS [27][28][29]. In two of these studies [28,29], equivalence between a 5-and a 10-day course of treatment with telithromycin has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Three randomised, controlled trials have been performed in patients with AMS [27][28][29]. In two of these studies [28,29], equivalence between a 5-and a 10-day course of treatment with telithromycin has been demonstrated. Here we present the results of a pooled analysis comparing the efficacy and tolerability of a 5-day regimen of telithromycin with that of a 10-day regimen of other antibacterial agents (amoxicillin-clavulanic acid and cefuroxime axetil) in the treatment of patients with AMS, with emphasis on bacteriological efficacy against key pathogens.…”
Section: Introductionmentioning
confidence: 99%